Volunteerism: A crosscutting and relational method to achieve the sustainable development goals - Devereux, Peter; Stocker, L.; Holmes, Kirsten (Edward Edgar, 2017)
© Janette Hartz-Karp and Dora Marinova 2017. All rights reserved. This chapter highlights the power of volunteerism as a method for achieving the Sustainable Development Goals. It emphasizes the importance of a relational approach in helping to energize and sustain locally appropriate strategies. Using case studies from Nicaragua, Honduras, El Salvador, Western Australia and the Philippines, it analyses methods to facilitate voluntary action that makes practical contributions. The case studies demonstrate that the nature and quality of relationships are key to successful voluntary action for sustainability. Volunteerism is shown to have increased the respective community’s capacity to tackle sustainability issues itself strengthening reciprocity, relationships, capacity and ownership. The four methodological principles highlighted for successful voluntary action embed mutual learning and accountability, reciprocal benefit, and foster synergies over trade-offs.